MAGNETIC WATER EFFECTS ON GROWTH AND SOME PHYSIOLOGICAL CHARACTERISTICS OF PAULOWNIA TOMENTOSA THUNB UNDER CADMIUM STRESS CONDITIONS - Abdullah, Ara F.; Albarznjii, Ikbal M. (Science Journal of University of Zakho, 2023)
Paulownia (Paulownia tomentosa) is considered as one of the world's fastest-growing species of trees and most widely used for commercial. This research was done as a factorial experiment in Koya city, Erbil, Iraq during 2021-2022 to study the effects of magnetic water (MW) at (0, 500,1000, 1500 and 2000) gauss and cadmium chloride (Cd) at (0, 3.33, 6.66 and 10 mg Kg-1soil) on some growth, physiological and biochemical properties of this plant. Results demonstrate that MW had non-significant differ regarding the survived and the velocity of cutting outgrowth compare to using tap water, whereas Cd application increased the velocity of cutting outgrowth. At least one of MW powers increased significantly each of plant leaf-area, stem diameter, shoot and root fresh weight and dry matter content, as well as all Cd concentrations increased the plants leaves number, leaf-area, stem diameter. Cd had more effects on roots than plant shoots, where it has non-significant effects on shoot high or dry matter, whereas it increased each of shoot and root fresh weight significantly compared to the control treatment. Low power MW (500 and 1000) gauss performed better than high powers (1500 and 2000) gauss in increasing the content of photosynthesis pigments. Utilizing magnetic water greatly enhanced total carotenoids and chlorophyll a, b, regardless to device power. Chlorophyll (a and b) were both significantly reduced by high Cd concentrations; however it was significantly increased at low concentrations as compared to other treatments. High power MW decreased significantly peroxidase enzyme activity and proline content whereas it decreased the percent of total carbohydrate compared to other treatments. Cd application decreased each of peroxidase enzyme activity, percent of total carbohydrate content, increased ascorbic acid and proline significantly in comparing to the control.
Keywords: Magnetic Water; Cadmium Stress; (i,j) - Sc - continuous; Peroxidase; Non-enzymatic Antioxidants